A study into Healthcare Service Location Problems, Location and Allocation in the Inanda area - Naidoo, Krishantha (Department of Civil Engineering, 2021)
Inanda is a predominantly rural area located on the northern coast of the province of KwaZulu Natal, South Africa. It is bordered by the areas of Phoenix, Verulam and Tongaat. In the context of healthcare accessibility in the Inanda area, the research aimed at investigating the problem in service location planning. This was done by investigating level of accessibility to existing healthcare facilities available to the residents of Inanda. Following the classification of accessibility problems, recommendations were made on where the facility locations can be improved or expanded to provide better accessibility in terms of location-allocation. Literature that has been reviewed focused on geographic location, GIS and accessibility measures, spatial accessibility, models used to test accessibility, service location planning and accessibility measures and metrics so as to provide a background and precedent for the service location planning carried out in the research. The research aimed to confirm that accessibility to the healthcare facilities is indeed a problem and to propose alternative strategies to overcome the accessibility problems identified. The access to healthcare service locations is dependent on a number of factors. Some of these factors include travel time and distance, available capacity at facilities, existing road network, and provision or lack thereof of an efficient public transport system. This accessibility to the health service locations was assessed by using available GIS information on healthcare facilities and using accessibility analysis to identify problems in terms of the services location as well as additional location-allocation of current and additional facilities. The analysis was based on the assumption that all service locations have unlimited capacity. Flowmap was used as the tool to analyse the GIS data and conduct various accessibility models. The different models were Expansion Model Analysis, Relocation Model Analysis, Catchment Area and Clinic Allocation Analysis, Catchment Profile, Market share of Supply Locations, Regular Proximity Count, Average Distance in Competition, Proximity Count in Competition, Lowest Mean Trip Cost Alternate, Second Best Catchment Distance and Pareto Cover Set. The results of the research showed that while the locations of the existing healthcare facilities are not ideal, most are accessible to the majority of the Inanda residents. The information on actual capacity available at each of the locations was not available at the time of the research being carried out and would be worthwhile to research in the future.